PENGARUH RASIO PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA SEKTOR INDUSTRI KIMIA DAN PAKAN TERNAK YANG TERDAFTAR DI BEI PERIODE 2014-2017 - SUTRA Aji NINGTYAS; Budi Wahono; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT Return is result obtained from on investment. Stock returns are influenced by various factors such as the ratio of profitability, liquidity, leverage, and company size. The purpose of this study was to determine the effect of the ratio of profitability, liquidity, leverage, and company size, on stock returns on service company Sub Sector chemical industry and animal feed. Sampling method in this research was purposive sampling and acquired 14 observational data as the sample. The data used in this research was secondary data. The data analysis technique used was multiple linier regression using SPSS 20.0. Analysis method used in this research is descriptive statistics, classical assumption test, multiple regression analysis, t test, and F test. The result of the study indicates a change in stock returns in companies that enter the list of research assuming variables Return on Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Logaritma Natural Total asset (LNTA). For Return on Asset (ROA) variable has positive and insignificant effect on stock return, Debt to Equity Ratio (DER) variable has positive and insignificant effect on stock return, Current Ratio (CR) variable has positive and insignificant effect on stock return, and for Logaritma Natural Total Asset (LNTA) variable has negative and insignificant effect on stock return. Keywords : Return on Asset (ROA), Debt to equity Ratio (DER), Current ratio (CR), Logaritma Natural Total Asset (LNTA), Stock Return.